How to do research the complete guide to designing and managing research projects - Moore, Nick (Library Association, 2000)
This manual provides practical help and guidance to anyone undertaking research. Issues addressed include: stating the objective; methods; the proposal; obtaining financial support; getting the project on the road; analysis; drawing conclusions; and disseminating the results.